Menggali Potensi Serta Nilai Ekonomi Budidaya Lebah Kelulut (Trigona Itama) Pada Kelompok Usaha Perhutanan Sosial Di Desa Tuwung Kabupaten Pulang Pisau Kalimantan Tengah - Grace Siska; Yanarita Yanarita; Meyka Yolanda; Reri Yulianti; Desy Natalia Koroh (HUTAN TROPIKA, 2023)
The social forestry enterprise group of stingless bee farming is a group that utilizes stingless bees for cultivation and already has a product, which is honey. The community managing the social forestry land is Tuwung Village, Pulang Pisau Regency, Central Kalimantan Province. The research aims to determine the potential and economic value, as well as the factors influencing the productivity of stingless bee honey. The research method used is qualitative descriptive method. The stingless bee farming enterprise in Tuwung Village produces 40 liters of honey from 33 hives, where the potential for stingless bee cultivation is still suboptimal. The economic value, as the income from honey sales in one year, amounts to Rp 10,000,000. The honey produced during one year totals 40 liters with a selling price of Rp 250,000 per liter, resulting in the income of this enterprise group still being suboptimal or relatively low.